2012
DOI: 10.4103/0974-8490.94736
|View full text |Cite
|
Sign up to set email alerts
|

Aloe barbadensis Mill. formulation restores lipid profile to normal in a letrozole-induced polycystic ovarian syndrome rat model

Abstract: Background:Polycystic ovarian syndrome (PCOS), characterized by ovulatory infertility and hyperandrogenism, is associated with metabolic complications such as dyslipidemia, insulin resistance and endothelial dysfunction. Almost 70% PCOS women have abnormal serum lipid levels (dyslipidemia) and 50% of these women are obese. Several classes of pharmacological agents have been used to manage dyslipidemia. However, studies have shown adverse effects associated with these drugs. In the light of alternate therapy, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…This is supported by the lower NEFA level found in the plasma of our AAM cows, reflecting a less-marked mobilization of lipid resources [34]. The reduced mobilization of body fats found in our study is consistent with the reduction in triglycerides and free fatty acids found in the plasma, liver, and kidney of murine models of Streptozotocin-induced diabetes and Letrozole-induced polycystic ovarian syndrome after feeding with Aloe barbadensis ethanolic extract [22,23]. Although obtained in murine models and using Aloe barbadensis instead of Aloe arborescens, these anti-hyperlipidemic effects observed against diabetes and polycystic ovary syndrome-related dyslipidemia suggests that the reduced NEFA concentration in the blood of our early lactating cows could depend on the effectiveness of WPH in managing body fat mobilization.…”
Section: Aloe Reduced Mobilization Of Body Reserves and Improved Lipisupporting
confidence: 87%
See 1 more Smart Citation
“…This is supported by the lower NEFA level found in the plasma of our AAM cows, reflecting a less-marked mobilization of lipid resources [34]. The reduced mobilization of body fats found in our study is consistent with the reduction in triglycerides and free fatty acids found in the plasma, liver, and kidney of murine models of Streptozotocin-induced diabetes and Letrozole-induced polycystic ovarian syndrome after feeding with Aloe barbadensis ethanolic extract [22,23]. Although obtained in murine models and using Aloe barbadensis instead of Aloe arborescens, these anti-hyperlipidemic effects observed against diabetes and polycystic ovary syndrome-related dyslipidemia suggests that the reduced NEFA concentration in the blood of our early lactating cows could depend on the effectiveness of WPH in managing body fat mobilization.…”
Section: Aloe Reduced Mobilization Of Body Reserves and Improved Lipisupporting
confidence: 87%
“…Similar experiments performed on diabetic rats [22] found Aloe to exert anti-diabetic effects by improving plasma insulin and reducing blood glucose concentration in fasting conditions and to manage dyslipidemia by restoring normal levels of lipoproteins and normal fatty acid composition in the liver and kidney. Other studies confirmed such an anti-hyperlipidemic effect [23] and found Aloe to reduce lipid peroxidation, inducing regenerative histological changes in the liver and kidney of diabetic rats [24].…”
Section: Introductionmentioning
confidence: 77%
“…It has phytocomponents with antihyperlipidemic effects and has shown efficacy also in management of PCOS but also the associated metabolic complications. 79,82 …”
Section: Clinical Efficacy and Mechanism Of Actionmentioning
confidence: 99%
“…Aloe vera (L.) Burm.f. reduced plasma levels of total cholesterol (TC), triglyceride (TG), and low density lipoprotein cholesterol (LDL-C); enhanced high density lipoprotein cholesterol (HDL-C) levels (Desai et al, 2012); normalized follicular growth; and recovered the estrous cycle (Maharjan et al, 2010). Atractylodes macrocephala Koidz.…”
Section: Individual Herbal Extractsmentioning
confidence: 99%
“…Herbal medicines were found to normalize female hormones, (Zangeneh et al, 2010;Rezvanfar et al, 2012;Jang et al, 2014;Yu et al, 2014;Gu et al, 2015;Zhou et al, 2016;Atashpour et al, 2017;Sun et al, 2017;Xia et al, 2017;Zhao et al, 2017;Jelodar et al, 2018), diminish male hormones (Yang et al, 2011;Rezvanfar et al, 2012;Yu et al, 2014;Gu et al, 2015;Zhou et al, 2016;Xia et al, 2017;Zhao et al, 2017;Jelodar et al, 2018), recover the estrous cycle (Mohamadin et al, 2010;Yang et al, 2011;Rezvanfar et al, 2012;Jang et al, 2014;Soumya et al, 2014;Yu et al, 2014;Gu et al, 2015;Lee et al, 2016;Zhou et al, 2016;Sun et al, 2017;Wang et al, 2017;Xia et al, 2017), ameliorate insulin resistance (Li et al, 2010;Mannerås et al, 2010;Yang et al, 2011;Desai et al, 2012;Wang et al, 2017;Zhao et al, 2017), and improve lipid metabolism in PCOS model (Mannerås et al, 2010;Desai et al, 2012;Soumya et al, 2014). The actions of herbal medicines and relevant outcomes are shown in …”
Section: The Actions Of Herbal Medicines For Treating Pcosmentioning
confidence: 99%